How Does it Feel to be Connected with Nature? A Qualitative Study of Meditation Practitioners in Sweden. - Yang,Romane Louise Aurélie (Master Thesis Series in Environmental Studies and Sustainability Science, 2023)
For the past centuries, human-nature relationships have deteriorated into a drastic disconnection, characterized by a lack of compassion for nature and insufficient action for mitigating environmental degradation. This study investigates connectedness with nature (CWN) among regular meditation practitioners. Nine in-depth interviews were conducted with meditation practitioners active in Sweden. The results suggest an expressed link between meditation and a state of CWN, during which participants practice being in the present moment and experience a sense of oneness, strong feelings and emotions and lastly, increased well-being. These experiences seem to be stronger for experienced practitioners. Implications for sustainability science are discussed as well as limitations of the study.
Keywords: meditation; connectedness with nature; mindfulness; human-nature relationship; Buddhism; Sweden; sustainability science